Theoretical unification in justice and beyond - Guillermina Jasso (Institute for the Study of Labor (IZA), 2007)
The goal of scientific work is to understand more and more by less and less. In this effort, theoretical unification plays a large part. There are two main types of theoretical unification - unification of different theories of the same field of phenomena and unification of theories of different fields of phenomena. Both types are usually a surprise - even when vigorously pursued, their form, when they finally appear, may differ radically from preconceptions. This paper examines a series of twenty-one unification surprises in the study of justice and beyond, sixteen in the study of justice and five in the unification of three fundamental sociobehavioral forces.
urn:nbn:de:101:1-20080416212
Keywords: 330; Gerechtigkeit; Soziale Gerechtigkeit; Wirtschaftstheorie; Wissenschaftliche Methode; Sozialer Status; Macht; Lebenszufriedenheit; Theorie